Economic efficiency of table grape production in Waterberg and Sekhukhune Districts, Limpopo Province, South Africa - Maponya, Naume Mapaseka (My University, 2020)
Table grape production plays an important role in the economy of many countries in Africa. It serves as a source of income for people who are engaged in its production and being one of the fields that is labour-intensive, thereby providing employment for many people. The aim of this study was to analyse economic efficiency of table grape production in Waterberg and Sekhukhune districts of Limpopo Province, South Africa. The study used primary data collected from semi-structured questionnaires. A sampling technique called snowball, was used in the study as this method assisted in getting those farmers that were not easily accessible. The analytical tools employed to analyse data included descriptive statistics and Stochastic Frontier Model. Findings from the study revealed that the average age of table grape farmers was 47 years. On average, household size for table grape farmers was found to be 5 members. Also, findings revealed that table grape farmers on average had a farming experience of 16 years. Average household income was found to be R47 600, 00. Furthermore, the study revealed that the average years of schooling for the table grape farmers was 15 years and only 67% of these farmers have acquired a tertiary educational level, while 33% have acquired secondary educational level. In terms of efficiency, farming experience (P<0,00), educational level (P<0,05) household size (P<0,10) and age of farmer (P<0,10) were associated with increased efficiency as they were found to be significant at 1%, 5% and 10% confidence level. The findings also revealed that quantity of grapes produced was positively influenced by Farm size (P<0,00), labour (P<0,00), pesticides used (P<0,05) , extension services (P<0,05) and fertilisers (P<0,05). Technical efficiency among farmers was found to range from 0.8 to 1, with a mean of 0.89, thus this indicated possibility of improvement in production. However, the allocative efficiency was found to range from 0.47 to 1, with a mean of 0.68, this clearly indicated that some farmers were finding it difficult to allocate their resources efficiently. On the other hand, it was found that economic efficiency ranged from 0.56 to 1, with a mean of 0.73, this indicated that most of the farmers were economically efficient. Meanwhile, some of the constraints faced by the table grape farmers included high electricity bills and labour costs, as such the introduction of prepaid electricity in the farms could reduce the strain they go through. Based on the findings from the study, it was recommended that, since the production of grapes is a male-dominated enterprise, women and youth should also participate. Participation could be encouraged through provision of learnership skills on the farms.
Thesis (M.Sc. (Agricultural Economics)) -- University of Limpopo, 2020
Keywords: Grape farming; Grape production; Employment; Technical efficiency; Industrial productivity; Economic efficiency; Grapes